Impact of eliminating visual input on sitting posture and head position in a patient with spatial neglect following cerebral hemorrhage: a case report. (3rd July 2021) - Chen, Peii; Motisi, Shannon E.; Cording, Christina; Ward, Irene; Jasey, Neil N.
ABSTRACT: Background: Spatial neglect is a neurocognitive syndrome. Affected individuals pay little or insufficient attention to the space contralateral to the injured cerebral hemisphere, often resulting in or exacerbating disability following an acquired brain injury. Eliminating visual input may increase attention toward the contralesional side of space, and improve symptoms of spatial neglect; however this has never been examined in a clinical setting. Objective: In this case report, we observed an individual demonstrate immediate and spontaneous postural changes once visual input was eliminated. Methods: The patient, a 53-year-old female, was admitted to a rehabilitation hospital after hemorrhagic stroke affecting her right basal ganglia and surrounding regions in the frontal lobe. She exhibited left-sided spasticity, severe right gaze preference, and stark rightward postural deviation. Neck passive range of motion was normal. Visual field integrity was inconclusive due to poor communication and impaired cognitive function. Contraversive pushing was ruled out. Results: Once visual input was eliminated by applying a blindfold, the patient turned to the left spontaneously, had more buttock contact on the left, and placed more weight toward the left side in a sitting posture. However, she returned to rightward deviation three minutes after blindfold removal. In addition, the patient's rehabilitation team reported that she was able to participate in more therapy activities with binocular occlusion than with eyes open. Conclusion: Binocular occlusion appeared to demonstrate an immediate, albeit transient, improvement in postural symmetry. The results warrant further research and exploration in clinical applicability.